Fernando vallejo: y la clausura ciudadanía estética de la literatura mundial - Nicholson, Brantley (CALLE14: revista de investigación en el campo del arte, 2011)
This article approaches current deliberations about World Literature from the perspective of the 20th century Colombian urban novel. In exploring the tension between local and global narrative histories, the author examines to what extent we can contend that World Literature and its sociocultural appendages lend themselves to emancipatory projects and to what extent they greatly oversimplify spaces of dense literary output. By placing Goethe’s Weltliteratur in the context of an aesthetically globalized Colombia and using the particularly thorny relationship between Fernando Vallejo and Gabriel García Marquez as a case study, this article maintains that international publishing houses and critical cultures create a limiting aesthetic citizenship that remains dominated by the marketing decisions of major publishing houses and the tastes of reading publics far removed from the context of “peripheral” bestsellers.